Quartz crystal microbalance based histidine sensor - Merve Sönmezler; Erdoğan Özgür; Handan Yavuz; Adil Denizli (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Herein, quartz crystal microbalance (QCM) biosensor is prepared for the detection of l-histidine by attachment of l-histidine imprinted poly(EGDMA-MAH/Cu(II)) nanoparticles on QCM electrode. The imprinted nanoparticles with the size of 86.43 nm were synthesized via miniemulsion polymerization reaction. Prepared QCM sensors were characterized with ellipsometer, contact angle measurements and FTIR. The thickness measurements demonstrated that the particle thin films were almost monolayer. l-histidine solutions with a concentration range between 6.44 μM and 225.6 μM were introduced to QCM system to determine the adsorption kinetics. Selectivity of the l-histidine imprinted nanoparticles were examined using d-histidine and l-tryptophan as competitor molecules. l-histidine imprinted QCM biosensors was also used for RNAase, lysozyme, cytochrome-C and BSA to investigate the competitive adsorption of surface histidine exposed proteins.